The Confucian self: an inquiry into the social foundations of Kongzi's Analects - Stahel, Vanessa, author; Harris, Eirik, advisor; MacKenzie, Matthew, committee member; Erickson, Peter, committee member (Colorado State University. Libraries, 2024)
Within ancient Chinese philosophy, the Analects of Kongzi is one of the most widely studied texts, having been read, re-read, and drawn upon for centuries. The text can offer worthwhile insights on its own grounds and may also provide a source of relevant discourse for contemporary investigations. The project at hand is an attempt to construct a plausible and consistent interpretation of the Analects, one which illuminates Kongzi's underlying conception of the self. To ground the text on an internally consistent interpretation, we will first look to two fundamental concepts within the text, li and ren. After establishing this groundwork, we will look more closely at Kongzi's conception of the self by examining his account of moral self-cultivation. As it will turn out, Kongzi's conception of the self is deeply relational; moral cultivation can only take place within a society and is performed for the purpose of bringing about the flourishing of both the individual and the community. We will conclude by offering some insights regarding the comparative possibilities between Kongzi's conception of the self and contemporary feminist theories of selfhood.
Keywords: Confucius; relational self; the Analects; political philosophy; ancient Chinese philosophy; social self